2017
DOI: 10.1111/cmi.12713
|View full text |Cite
|
Sign up to set email alerts
|

SolubleN-ethylmaleimide-sensitive factor attachment protein receptors required duringTrypanosoma cruziparasitophorous vacuole development

Abstract: Trypanosoma cruzi, the etiologic agent of Chagas disease, is an obligate intracellular parasite that exploits different host vesicular pathways to invade the target cells. Vesicular and target soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) are key proteins of the intracellular membrane fusion machinery. During the early times of T. cruzi infection, several vesicles are attracted to the parasite contact sites in the plasma membrane. Fusion of these vesicles promotes the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
(105 reference statements)
1
18
0
Order By: Relevance
“…The abolition of this phenomenon, known as reversal infection, by allowing the lysosomal fusion to TcPV, is a key process for the retention of T. cruzi inside the host cell [26]. In agreement with this, further studies from our group demonstrated that the SNARE VAMP7 and its partner Vti1b, both components of the molecular machinery that promotes lysosomal fusion, are required during T. cruzi vacuole development and, as a consequence, for the parasite infection [27]. We have also shown that migration of VAMP7 positive vesicles to the TcPV depends on KIF5, a motor protein belonging to the superfamily of kinesins.…”
Section: Introductionsupporting
confidence: 57%
“…The abolition of this phenomenon, known as reversal infection, by allowing the lysosomal fusion to TcPV, is a key process for the retention of T. cruzi inside the host cell [26]. In agreement with this, further studies from our group demonstrated that the SNARE VAMP7 and its partner Vti1b, both components of the molecular machinery that promotes lysosomal fusion, are required during T. cruzi vacuole development and, as a consequence, for the parasite infection [27]. We have also shown that migration of VAMP7 positive vesicles to the TcPV depends on KIF5, a motor protein belonging to the superfamily of kinesins.…”
Section: Introductionsupporting
confidence: 57%
“…Importantly, studies detecting the secretion of lysosomal enzymes or surface localisation of the lysosomal transmembrane protein LAMP1 demonstrated that trypanosomes induce calcium‐mediated exocytosis through fusion of lysosomes with the plasma membrane (Rodriguez, Webster, Ortego, & Andrews, ). Recent data indicate that this fusion event is mediated by VAMP7, a v‐SNARE present on lysosomes (Cueto et al, ). Collectively, these results reveal that T. cruzi mobilises lysosomes, resulting in exocytosis and pathogen uptake into host cells.…”
Section: Exocytosis and Microbial Pathogenesismentioning
confidence: 99%
“…After membrane fusion, the soluble NSF protein and soluble αSNAP bind to the inactive cis‐SNARE configuration. NSF then hydrolyses and dissociates the complex so that it is available for the next fusion (Ungar & Hughson, ; Cueto et al , ). STX1, SNAP‐25 and VAMP1 were the first SNAREs to be discovered.…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%
“…Vti1p, VAM3p, and VAM7p are vacuolar SNARE proteins, which are the target of the HOPS complex that enhances fusion efficiency in yeast (Wang et al , ). There are nine v‐SNAREs that have been identified in mammals, of which VAMP3 and VAMP7 are involved in endosomal membrane fusion (Cueto et al , ). VAMP3 is present on early and recycling endosomes, and regulates amphisome formation, while VAMP7 is present on late endosomes and post‐Golgi secretory vesicles, and modulates autolysosome formation.…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%